Critical Role of Lkb1 in the Maintenance of Alveolar Macrophage Self-Renewal and Immune Homeostasis - Wang, Qianqian; Chen, Song; Li, Tengda; Yang, Qiongmei; Liu, Jingru; Tao, Yuan; Meng, Yuan; Chen, Jiadi; Feng, Xiaoming; Han, Zhongchao; Shi, Mingxia; Huang, Huifang; et al. (Frontiers in Immunology, 2021)
Alveolar macrophages (AMs) are pivotal for maintaining lung immune homeostasis. We demonstrated that deletion of liver kinase b1 (Lkb1) in CD11c+ cells led to the greatly reduced AMs abundance in lung due to the impaired self-renewal of AMs, but not the impeded pre-AMs differentiation. Mice with Lkb1-deficient AMs had deteriorated diseases during airway Staphylococcus. aureus (S. aureus) infection and allergic inflammation, with the excessive accumulation of neutrophils and severer pathology in lung. The drug-mediated AM-depletion experiments in wild-type mice indicated a causative reason of AMs reduction in aggravated diseases in Lkb1 conditional knockout mice. Transcriptomic sequencing also revealed that Lkb1 inhibited the pro-inflammatory pathways including IL-17 signaling and neutrophils migration, which might also contribute to the protective function of Lkb1 in AMs. We thus identified Lkb1 as a pivotal regulator to maintain self-renewal and immune function of AMs.